Pengetahuan dan Sikap Perawat terhadap Tindakan Triase di Instalasi Gawat Darurat: Nurses' Knowledge and Attitude towards Triage Actions in the Emergency Department - Sahrudi; Akhyarul Anam (Fakultas Keperawatan Universitas Andalas, 2021)
Triage is a significant activity in an Emergency Room (ER). The triage nurture is the principal individual the patient experiences when going to the crisis room. Medical attendant's information on triage is key in dynamic in triage terms. Compelling dynamic can influence the accomplishment of activities taken to patients. This examination intends to decide the information and mentalities of medical caretakers towards triage in the ER RSUD Koja. The examination strategy utilizes an illustrative quantitative cross-sectional investigation led at the ER. The exploration instrument was as an organized poll created by specialists and depended on existing writing on triage in the ER. The testing method in this investigation is complete inspecting with an example size of 60 respondents. The outcomes indicated a noteworthy connection between the degree of information on crisis medical caretakers to triage with P-value = 0.030 and OR = 0.99. There is a noteworthy connection between the perspectives of crisis medical attendants towards triage with P- value = 0.002 and OR = 9.8. This investigation suggests that medical caretakers consistently go to preparing identified with crisis activities so the accomplishment of advancement of administrations in the crisis room as the front watchman of a hospital.